2007
DOI: 10.1016/j.jmr.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of hyperpolarized gas diffusion at very short time scales

Abstract: We present a new pulse sequence for measuring very-short-time-scale restricted diffusion of hyperpolarized noble gases. The pulse sequence is based on concatenating a large number of bipolar diffusion-sensitizing gradients to increase the diffusion attenuation of the MR signal while maintaining a fundamentally short diffusion time. However, it differs in several respects from existing methods that use oscillating diffusion gradients for this purpose. First, a wait time is inserted between neighboring pairs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…By contrast, oscillating gradient spin echo (OGSE) methods at high frequencies can probe short diffusion times and, hence, have the potential to detect changes over much shorter length-scales [16]. The OGSE method has been successfully implemented experimentally to probe structural information including short length scales in packed beads [17], in vivo in ischemic rat brain [18], to study hyperpolarized gas diffusion [19] and to characterize tumors [20]. However, due to the relatively complicated gradient waveforms used in the OGSE method, analytical descriptions of DW signals with OGSE have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, oscillating gradient spin echo (OGSE) methods at high frequencies can probe short diffusion times and, hence, have the potential to detect changes over much shorter length-scales [16]. The OGSE method has been successfully implemented experimentally to probe structural information including short length scales in packed beads [17], in vivo in ischemic rat brain [18], to study hyperpolarized gas diffusion [19] and to characterize tumors [20]. However, due to the relatively complicated gradient waveforms used in the OGSE method, analytical descriptions of DW signals with OGSE have not previously been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that 3 He ADC obtained at millisecond diffusion times can distinguish normal from emphysematous tissue and correlates with mean linear intercept histology, an accepted measure of alveolar damage (12,13). 3 He ADC values obtained at sub-millisecond diffusion times (14) are expected to be even more sensitive to emphysema, especially in small animals. At longer diffusion times on the order of seconds, 3 He ADC is expected to reflect changes in lung anatomy over much larger length scales on the order of centimetres.…”
mentioning
confidence: 99%
“…The behavior of D in the presence of restrictions as a function of time is a well studied problem and generally used to obtain information on the surface to volume ratio [15,24,25]. Although, Eq.…”
Section: Diffusion Limited Sensitivity and Resolutionmentioning
confidence: 99%